Kajian Keteknikan Sistem NFT (Nutrient Film Technique) dengan Rekayasa Debit dan Kemiringan Talang pada Pertumbuhan dan Hasil Tanaman Kailan (Brassica Oleraceae L.) - Veronika, Reni; Tooy, Dedie; Ludong, Daniel P. M. (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2025)
Hydroponics is a method of cultivating plants without using soil, but rather using a growing medium and nutrient solution. One commonly used hydroponic system is the Nutrient Film Technique (NFT), in which a nutrient solution is flowed in a thin, continuous stream along a sloping gutter. This study aimed to examine the effect of varying flow rate and gutter slope on the growth and yield of kale (Brassica oleraceae L.) in an NFT hydroponic system in a greenhouse. The study used two levels of gutter slope (5.24% and 8.75%) and three levels of flow rate (0.5 L/minute, 1.5 L/minute, and 2.5 L/minute) with a completely randomized design (CRD) with two factors and three replications. Observed parameters included plant height, number of leaves, fresh weight, pH, and nutrient solution concentration (ppm). The results showed that the 8.75% slope treatment with a 2.5 L/minute flow rate produced the best growth, with an average plant height of 69.89 cm and a fresh weight of 86 g. Although the difference in fresh weight was not statistically significant, the treatment combination provided optimal vegetative growth. The nutrient solution pH ranged from 5.3–6.3 and ppm between 1060–1240, which is still suitable for leafy plant growth. Therefore, a combination of an 8.75% slope and a flow rate of 2.5 L/min is recommended as the optimal NFT system design for kale..